2019
DOI: 10.1504/ijvcm.2019.096538
|View full text |Cite
|
Sign up to set email alerts
|

An integrated structural modelling and MICMAC analysis for supply chain disruption risk classification and prioritisation in India

Abstract: Supply chain disruptions can have severe impacts on a firm. Realising the importance of the matter, this study aims at identifying and prioritising the risks associated with supply chain disruption as faced by Indian manufacturing sector. A two-phase methodology is used for achieving the objectives-the first phase involves the identification and finalisation of supply chain disruption risks through literature review and expert opinion using Delphi technique, and the second phase involves deriving the interrela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…The decision makers' profile is shown in Table 2. In the second phase, the authors performed the FDM to find the CRF's with help of the decision maker's assessment from telecom companies in India [100]. Nine CRF's are determined based on the threshold value (0.65) of the FDM.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The decision makers' profile is shown in Table 2. In the second phase, the authors performed the FDM to find the CRF's with help of the decision maker's assessment from telecom companies in India [100]. Nine CRF's are determined based on the threshold value (0.65) of the FDM.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, there are few studies conducted to analyze risk factors in the current literature. For example, Alora and Barua [100] had used MIC-MAC to disruption risk classification and prioritization of supply chain in India. And, another article classified risks prioritization in global supply networks using MICMAC method [111].…”
Section: Categorizing Risk Factors Impacting Ssc Of Indian Telecommun...mentioning
confidence: 99%
“…Few studies have been found in the milieu of developing countries, such as Business Process Outsourcing (Malik et al, 2012), Pharmaceutical Industry, the Information and Technology Sector, Health Care Sector, Family Business (Bamel & Bamel, 2018), Agriculture Sector (Velu, 2017), Software Industry (Dayasindhu, 2002), Small and Medium‐Sized Enterprises (Alora & Barua, 2019), Wastewater Industry (Gebauer et al, 2012), and Life Insurance (Roy & Khokle, 2016). Most of the contextual settings reside in developed countries.…”
Section: Tccm Analysismentioning
confidence: 99%
“…The first stage involves the identification and finalization of supply chain disruption risks through literature review and expert opinion using the Delphi method. In addition, the second stage includes the extraction of the relationships between risk factors using interpretive structural modeling (ISM) (27). Tang studied robust strategies for the reduction of supply chain disruptions and presented robust strategies with two properties (28).…”
Section: Original Articlementioning
confidence: 99%